The Quality of Broiler Chicken Meat Given Bean Sprouts Waste in Rations During Storage - Ni Ketut Sri Rukmini; Ni Ketut Mardewi; I Gusti Ayu Dewi Seri Rejeki (Formosa Journal of Science and Technology, 2023)
The purpose of this study was to determine the quality of broiler chicken meat which was given a ration containing fermented bean sprout waste flour during storage. This study used a completely randomized design (CRD) with 2 factors, namely factor 1 which consisted of P0 (control ration without the addition of fermented bean sprout waste flour), P1 (ration containing 3% fermented bean sprout waste flour), P2 (ration containing 6% fermented bean sprout waste flour, and P3 (ration containing 9% fermented bean sprout waste flour).The interaction of fermented bean sprout waste and storage time showed no significant effect (P>0.05) on broiler meat quality. Storage time of broiler chicken meat at temperature 8˚C with good quality is 8 days.